Representasi Profesional Petani Padi-Sawah dalam Hubungannya dengan Praktek Pengendalian Hama - Katrina Pandjaitan, Nurmala (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2010)
The purpose of this research is to apprehend plant disease management practices from a psyhosocial viewpoint. Is there any relationship between plant disease management practices and the professional representations of the farmers? What influence does professional context have in this relationship? How does participation in SLPHT, used to spread IPM Practices, influence rice farmers in plant disease management? The relationship between professional representations and pest management practices varies depending on the professional context. When institutional coercion is marked, it is the legal prescriptions which influence the relationship between professional representations and practices. Inversely, when institutional coercion is less marked, professional representations guides practices. Participation in SLPHT is unrelated to plant disease management by the rice farmers. This research aims to contribute to the study of adult training by showing how the professional context can influence the adoption of innovation.